An observational study of older patient specialling in acute hospital settings. (18th May 2020) - Cook, Jacquelene; Palesy, Debra; Lapkin, Samuel; Chenoweth, Lynn
Abstract: Background: During hospitalisation, older people can quickly become disoriented and agitated. In these instances, 'specialling', involving close monitoring and observation of the person to prevent accidents, injuries and clinical deterioration is often required. Despite the widespread practice of older patient specialling, there is no evidence of the best model, or any clear guidelines around the essential requirements for this practice. Aim: This study aimed to examine specialling practices for hospitalised older patients in acute aged care wards. Method: Quantitative and qualitative data were obtained in an observational study of specialling practices for hospitalised older patients. Two validated observational tools were used to collect data on nursing care provided during specialling and patient responses to specialling over a three‐month period. Findings: A total of 58 observations were undertaken of specialling practices for 12 hospital patients aged 65 years and over in four acute aged care wards. Delirium was the most common reason for older patient specialling. Most specialling was undertaking by Assistants in Nursing. Specialling interactions and responses were mainly positive. Positive specialling practices occurred when the staff special was familiar with the older patient and the ward in which specialling occurred. Specialling practices differed in relation to, the type of care required, the presence of the patients' personal possessions in their immediate surroundings, the presence of medical devices, patient acuity and general ward busyness. Conclusion: These findings suggest that specialling practices differ according to patient need and that the staff member's familiarity with the ward and their patients are important factors in positive older patient specialling. The specialling role needs much clearer definition, including the type of educational preparation and workload support that is appropriate to ensure safe and quality care.